1996
DOI: 10.1289/ehp.104-1469669
|View full text |Cite
|
Sign up to set email alerts
|

Teplice program--the impact of air pollution on human health.

Abstract: The aim of the Teplice Program is to investigate and assess the impact of air pollution on the health of the population in the district of Teplice, Czech Republic. Characterization of the air pollutants demonstrated unusually high concentrations during winter inversions of fine particles dominated by acidic sulfates, genotoxic organic compounds, and toxic trace elements. The major source of airborne fine particles is the burning of coal for heating and power. Human exposure and biomarker studies demonstrated l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
61
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 35 publications
0
61
0
1
Order By: Relevance
“…Others have shown that prenatal exposure to maternal tobacco smoke is associated with effects on cognitive development at age 3 years (28 (29,(31)(32)(33)(34)(35)(36) There is evidence in humans that PAH, fine particles, and other pollutants from burning of coal may adversely affect birth outcomes. There was an excess prevalence of low birth weight and premature births in a polluted district of the Czech Republic (Teplice) compared to Prachatice, where pollution was low (37). These adverse effects were more common in infants conceived in the winter months and whose mothers were smokers (21).…”
Section: Enhanced Susceptibility Of the Developing Fetus And Infantmentioning
confidence: 99%
“…Others have shown that prenatal exposure to maternal tobacco smoke is associated with effects on cognitive development at age 3 years (28 (29,(31)(32)(33)(34)(35)(36) There is evidence in humans that PAH, fine particles, and other pollutants from burning of coal may adversely affect birth outcomes. There was an excess prevalence of low birth weight and premature births in a polluted district of the Czech Republic (Teplice) compared to Prachatice, where pollution was low (37). These adverse effects were more common in infants conceived in the winter months and whose mothers were smokers (21).…”
Section: Enhanced Susceptibility Of the Developing Fetus And Infantmentioning
confidence: 99%
“…Findings from animal studies have provided evidence of an association between air pollution and reproductive and developmental anomalies (Bignzmi et al 1994;Falkner 1986;Kavlock et al 1979Kavlock et al , 1980. Until recently, however, few epidemiologic studies have examined the potential effects of ambient air pollution on birth outcomes (Bobak , 2000Bobak and Leon 1999;Dejmek et al 1999;Dolk et al 2000;Ritz and Yu 1999;Ritz et al 2000;Rogers et al 2000;Sram et al 1996;Wang et al 1997;Woodruff et al 1997;Xu et al 1995).…”
mentioning
confidence: 99%
“…We examined the influence of selfreported active and passive smoking on fetal growth in a retrospective epidemiologic study in the frame of a wider project named the Teplice Program (18). The design of the present study enabled us to evaluate the effects of ETS on the fetal growth of infants delivered by nonsmoking mothers as well as by mothers who smoked during the different gestational phases (AS mothers).…”
mentioning
confidence: 99%